Alcune riflessioni sull’analisi guardiniana del pensiero di S. Bonaventura - Vinco, Roberto (Alpha omega, 2019)
Summary: In this contribution, I shall present key aspects of the interpretation of Saint Bonaventure’s thought developed by Romano Guardini. The central point upon which I shall concentrate is the “mystical orientation” of the Serafic Doctor's perspective, which also shapes his metaphysical point of view. In the second part, I shall show that some elements of the developed “Bonaventurian standpoint” are also central to the perspective which underpins Guardini’s conception of liturgy. - Keywords: Metaphysics, Natural Theology, mysticism, Guardini, Bonaventura. - Parole chiave: metafisica, teologia naturale, mistica, Guardini, Bonaventura.
Gesehen am 07.04.2021